Sound Citizens Australian Women Broadcasters Claim their Voice, 1923-1956 - Fisher, Catherine (ANU Press, 2021)
In 1954 Dame Enid Lyons, the first woman elected to the Australian House of Representatives, argued that radio had 'created a bigger revolution in the life of a woman than anything that has happened any time' as it brought the public sphere into the home and women into the public sphere. Taking this claim as its starting point, Sound Citizens examines how a cohort of professional women broadcasters, activists and politicians used radio to contribute to the public sphere and improve women's status in Australia from the introduction of radio in 1923 until the introduction of television in 1956. This book reveals a much broader and more complex history of women's contributions to Australian broadcasting than has been previously acknowledged. Using a rich archive of radio magazines, station archives, scripts, personal papers and surviving recordings, Sound Citizenstraces how women broadcasters used radio as a tool for their advocacy; radio's significance to the history of women's advancement; and how broadcasting was used in the development of women's citizenship in Australia. It argues that women broadcasters saw radio as a medium that had the potential to transform women's lives and status in society, and that they worked to both claim their own voices in the public sphere and to encourage other women to become active citizens. Radio provided a platform for women to contribute to public discourse and normalised the presence of women's voices in the public sphere, both literally and figuratively.